PENGARUH BEBAN KERJA, PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. PRIMA MITRA PIRANTI SIDOARJO - Ketut Witara; Bima Surya Setiyawan (STIE Mahardhika, 2023)
Competition of cleaning service company for aircraft is increasing, so that PT. Prima Mitra Piranti in Sidoarjo must improve the performance of its employees in order to be able to improve company performance. The purpose of this study was to determine and analyze the effect of workload, training and work discipline on employee performance. This research is a quantitative research by taking a sample of 41 employees of PT. Prima Mitra Piranti in Sidoarjo with saturated or census sampling technique. This study used the Multiple Regression Analysis method and data processing using SPSS obtained the results of Instrument testing the results of which passed the Validity Test and Reliability Test, then the Classical Assumptions Test obtained the results of passing the Normality Test, Heteroscedasticity Test and Multicollinearity Test. The coefficient of determination (Adjusted R Square) is 0.852 or 85.2%, while 14.8% indicates that employee performance is influenced by other variables. The multiple regression equation is Y = 0.653 - 0.429.X1 + 0.696.X2 + 0.719.X3. The conclusions of the research are: 1. Workload has a negative and significant effect on employee performance. 2. Training has a positive and significant effect on employee performance. 3. Work discipline has a positive and significant effect on employee performance. 4. Workload, training and work discipline simultaneously have a significant effect on employee performance.